The Effect of Prednisolone on miR 15a and miR16-1 Expression Levels and Apoptosis in Acute Lymphoblastic Leukemia Cell Line: CCRF-CEM - Azimi, A.; Hagh, M. F.; Yousefi, B; Rahnama, M. A.; Khorrami, A.; Heydarabad, M. Z.; Najafpour, M.; Hallajzadeh, J.; Ghahremani, A. (Drug Research, 2016)
Background: Glucocorticoids are probably the most important drugs in the treatment of childhood acute lymphoblastic leukemia (ALL). Prednisolone exerts its effect by induce apoptosis in lymphoid lineage cells. Micro RNAs are 18–24 nucleotides RNA implicated in the control of essential biological functions, including apoptosis. In the following study, the effect of prednisolone on the expression of miR 15a & miR16-1 and apoptosis in the CCRF-CEM cell line is investigated.Methods: The cell line of CCRF-CEM was cultured in standard conditions. The changes in the miR 15a and miR 16-1 expression levels were determined by Real Time-PCR technique. Also, the apoptosis is evaluated by flow cytometry using Annexin V and PI staining.Results: This study revealed that, the prednisolone induced apoptosis in a time dependent manner. Prednisolone in concentration of 700 µM was significantly increased the expression of miR 16-1 and miR 15a after 24 h and 48 h treatment (p<0.05).Conclusion: prednisolone-induced apoptosis might be mediated by up-regulation of these 2 miRNAs in CCRF-CEM cells.
Keywords: ALL; prednisolone; miR 15a; miR 16-1; apoptosis